Downloading digital video games: predictors, moderators and consequences - Phau, Ian; Liang, Johan (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to investigate how personal and social factors influence attitudes towards downloading pirated games from the internet. It also examines the moderators between attitudes and intention to download pirated digital video games. Design/methodology/approach – The research was conducted using convenience samples in a large university in Western Australia. The data were analysed mostly through regression models. Findings – Self-efficacy, affect and moral judgement have significant influences upon attitudes towards downloading pirated games from the internet. Conversely, habits, facilitating conditions and social factors do not have significant influences upon attitudes towards downloading pirated games from the internet. In addition, attitudes towards downloading pirated digital video games from the internet have a significant influence upon the intention to download pirated digital video games from the internet. It is also found that the level of internet usage, the level of internet time spent and the internet speed do not moderate the relationship between attitudes and intention to download pirated games from the internet. Research limitations/implications – The major limitation is the use of a convenience sample. Therefore, future research should replicate and extend this study by using more valid random samples. In addition, qualitative approach, field experiment and foolspeed campaign analysis need to be considered to gain a better understanding of why internet users indulge in games piracy.Practical implications – Authorities should create awareness campaigns about digital video games piracy to alert the public about the risk of being caught and the consequence of unethical behaviour. Managers, marketers and policy makers should collaborate to combat piracy to prevent illegal downloading of free pirated games in the future. Originality/value – The paper assesses the impact of six antecedents and the attitudes towards downloading pirated digital video games from the internet that will lead to the intention to download pirated digital video games from the Internet.